Abdominal aneurysm sac thrombus CT density and volume after EVAR: which association with underlying endoleak? - Matthias Lembrechts; Lucas Desauw; Walter Coudyzer; Annouschka Laenen; Inge Fourneau; Geert Maleux (European Radiology Experimental, 2024)
Abstract Background Our aim was to analyse abdominal aneurysm sac thrombus density and volume on computed tomography (CT) after endovascular aneurysm repair (EVAR). Methods Patients who underwent EVAR between January 2005 and December 2010 and had at least four follow-up CT exams available over the first five years of follow-up were included in this retrospective single-centre study. Thrombus density and aneurysm sac volume were calculated on unenhanced CT scans. Linear mixed models were used for data analysis. Results Out of 82 patients, 44 (54%) had an endoleak on post-EVAR contrast-enhanced CT. Thrombus density significantly increased over time in both the endoleak and non-endoleak groups, with a slope of 0.159 UH/month (95% confidence interval [CI] 0.115–0.202), p < 0.0001) and 0.052 UH/month (95% CI 0.002–0.102, p = 0.041). In patients without endoleak, a significant decrease in aneurysm sac volume was identified over time (slope -0.891 cc/month, 95% CI -1.200 to -0.581); p < 0.001) compared to patients with endoleak (slope 0.284 cc/month, 95% CI -0.031 to 0.523, p = 0.082). The association between thrombus density and aneurysm sac volume was positive in the endoleak group (slope 1.543 UH/cc, 95% CI 0.948–2.138, p < 0.001) and negative in the non-endoleak group (slope -1.450 UH/cc, 95% CI -2.326 to -0.574, p = 0.001). Conclusion We observed a progressive increase in thrombus density of the aneurysm sac after EVAR in patients with and without endoleak, more pronounced in patients with endoleak. The association between aneurysm volume and thrombus density was positive in patients with and negative in those without endoleak. Relevance statement A progressive increase in thrombus density and volume of abdominal aortic aneurysm sac on unenhanced CT might suggest underlying endoleak lately after EVAR. Key Points Thrombus density of the aneurysm sac after EVAR increased over time. Progressive increase in thrombus density was significantly associated to the underlying endoleak. The association between aneurysm volume and thrombus density was positive in patients with and negative in those without endoleak. Graphical Abstract